“I Believe I Can Speak”: English-Speaking Self-Efficacy and Its Sources among Indonesian High School Students - Christina Helen Indarto; Adaninggar Septi Subekti (VELES Voices of English Language Education Society, 2026)
English-speaking self-efficacy (E-SSE) plays a crucial role in EFL learning because students’ willingness to speak is shaped not only by linguistic knowledge but also by their belief in their ability to communicate successfully. This study examined Indonesian senior high school students’ level of E-SSE and identified the factors contributing to its development. Using a mixed-methods design, data were collected from 160 students at a private senior high school in Java, Indonesia, through a paper-based E-SSE questionnaire and semi-structured interviews. Six students were purposively selected for interviews based on their self-efficacy levels, representing low, moderate, and high categories. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through thematic analysis. The findings showed that students generally reported a moderate level of English-speaking self-efficacy, indicating that their confidence in speaking English was present but not yet stable across speaking situations. Students felt relatively more capable of speaking with emotion and using appropriate language, but less confident when speaking fluently, speaking under nervous conditions, or responding to unfamiliar topics. Three contributing factors emerged from the qualitative data. Encouragement from family and friends strengthened students’ confidence; observing others’ success was both inspiring and intimidating; and positive self-talk helped students manage self-doubt and sustain belief in their speaking ability. These findings suggest that E-SSE is shaped by social support, interpretation of peer models, and learners’ internal regulation. Pedagogically, teachers should provide low-anxiety speaking tasks, constructive peer encouragement, guided reflection, and positive self-talk activities to strengthen students’ speaking confidence.